2012
DOI: 10.1002/humu.22223
|View full text |Cite
|
Sign up to set email alerts
|

FLT4/VEGFR3and Milroy Disease: Novel Mutations, a Review of Published Variants and Database Update

Abstract: Milroy disease (MD) is an autosomal dominantly inherited primary lymphoedema. In 1998, the gene locus for MD was mapped to 5q35.3 and mutations in VEGFR3 (FLT4) were identified as being responsible for the majority of MD cases. Several This finding confirms that this mouse lineage is an excellent model for MD. All the data reviewed here has been submitted to a database based on the Leiden Open (source) Variation Database (LOVD) and is accessible online at www.lovd.nl/flt4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 56 publications
2
67
1
Order By: Relevance
“…Missense mutations in the tyrosine kinase domain of VEGFR3 are responsible for about 70% of cases of an autosomal dominant primary congenital lymphedema known as Milroy disease (22,23). Additionally, a homozygous recessive mutation has been identified in a lymphedema patient (24,25).…”
Section: Lymphangiogenic Pathways and Mechanisms Vegfc/d And Vegfr3mentioning
confidence: 99%
“…Missense mutations in the tyrosine kinase domain of VEGFR3 are responsible for about 70% of cases of an autosomal dominant primary congenital lymphedema known as Milroy disease (22,23). Additionally, a homozygous recessive mutation has been identified in a lymphedema patient (24,25).…”
Section: Lymphangiogenic Pathways and Mechanisms Vegfc/d And Vegfr3mentioning
confidence: 99%
“…VEGFR-3 tyrosine kinase activity is crucial for lymphatic vessel growth (Zarkada et al 2015), but recently there were reported controversial data concerning its involvement in angiogenesis, mainly by controlling tip to stalk conversion at vessel fusion site (Nilsson et al 2010;Tammela et al 2011) and also by supporting sprouting, vessel branching, and endothelial cell proliferation (Cao et al 1998;Tammela et al 2008). In 2013, Gordon et al (2013b) reported for the first time in humans that VEGFR-3 mutations or impairment of its phosphorylation during embryonic lymphangiogenesis correlated with mutation in VEGF-C (Gordon et al 2013a) is causative for a defective lymphatic vessel development and primary lymphedema from Milroy disease. The VEGF-C/VEGFR-3 axis is expressed not only by lymphatic endothelial cells but also by a variety of human tumor cells.…”
Section: Lymphangiogenesis: Step By Step From Friendship To Hostilitymentioning
confidence: 99%
“…15,16 Granulocyte macrophage-colony-stimulating factor (GM-CSF) autoantibodies and mutations in the GM-CSF receptor may lead to PAP, 17 whereas FLT4 and other mutations may underlie congenital lymphedema. 18 Considerable clinical heterogeneity exists among patients with GATA2 deficiency. Age at disease onset ranges from early childhood to late adulthood, and clinical presentations range from asymptomatic to life-threatening infections, leukemia, and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%